2008
DOI: 10.1017/s0033291708004091
|View full text |Cite
|
Sign up to set email alerts
|

The epidemiology of depression in metropolitan China

Abstract: Background-Previous surveys on depression in China focused on prevalence estimates without providing a detailed epidemiological profile.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
80
1
1

Year Published

2009
2009
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 135 publications
(88 citation statements)
references
References 31 publications
6
80
1
1
Order By: Relevance
“…Prior research has demonstrated reasonable accuracy of such self-reported measures (Kriegsman et al 1996). This dichotomous variable has previously been found to be a valid predictor depression among Chinese populations (Lee et al 2009). …”
Section: Methodsmentioning
confidence: 83%
See 2 more Smart Citations
“…Prior research has demonstrated reasonable accuracy of such self-reported measures (Kriegsman et al 1996). This dichotomous variable has previously been found to be a valid predictor depression among Chinese populations (Lee et al 2009). …”
Section: Methodsmentioning
confidence: 83%
“…In addition, previous studies of Chinese immigrants consistently found physical health status to be a strong predictor of depression (Lai 2004;Lee et al 2009). …”
Section: Predictors Of Depression Among Chinese Americansmentioning
confidence: 87%
See 1 more Smart Citation
“…An epidemiological study also reported that the weighted prevalence estimates for MDD in a southwestern city (Kunming) in China were 1.96% (lifetime), 1.09% (1 year), and 0.93% (1 month) [8]. The lifetime prevalence estimate for Shanghai city is 3.6% [9] and that in Taiwan is 1.2% [10]. Another recent investigation reported that the prevalence rates for MDD among university undergraduates were 3.9% (lifetime), 2.4% (1 year), and 0.4% (1 month) in Mainland Chinese [11].…”
Section: Epidemiology Of Mdd In Chinamentioning
confidence: 98%
“…The recorded morbidity of mental health illness in mainland China is low (229). However, migrants may be highly stressed during the process of migrating and settling due to language difficulties, discriminations and under employment (230)(231)(232).…”
Section: Self-assessed Life Satisfaction Levelmentioning
confidence: 99%